DOWN SYNDROME AND ITS AGE-RELATED CHARACTERISTICS - Khudjanova Muattar Absalamovna; Shukhrat Pulodov; Khadichabonu Jurakulova (Web of Journals Publishing, 2024)
This article provides information on the origins, history, causes, clinical presentation, etiology, age-related characteristics, and developmental stages of Down syndrome.
Keywords: Down syndrome, leukemia, Alzheimer's, chromosome, autosome, anomaly, trisomy, mosaicism, translocation, cognitive, hippocampus, cerebellum.